Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Daerah Di Kota Makassar - Ayu Astuti; Veronika Sari Den Ka; Sri Nirmala Sari (Income Journal: Accounting, Management and Economic Research, 2022)
Regional Tax is a mandatory levy paid by the population of a certain area to the regional government that will be used for the benefit of the regional government and the public interest. To optimize local tax revenue, several related variables of population, inflation and Gross Regional Domestic Product. This study aims to determine the effect of population on local tax revenues, the influence of inflation on local tax revenues and the effect of Gross Regional Domestic Product on local tax revenue in the City of Makassar. Data analysis techniques used are multiple linear regression. The results of the study show that the population and inflation do not affect the local tax revenue and the Gross Regional Domestic Product affects the local tax revenue in Makassar City. Makassar City's population continues to grow but does not cause high inflation so it does not affect the level of local tax revenue. Makassar City's residents are indicated to be productive so as to increase local tax revenue.